Notes on Iberian Mutillidae (Hymenoptera) part I: a new species, new records and some taxonomic and faunistic remarks - Parejo-Pulido, Daniel; Romano, Marcello (Zootaxa, 2024)
In this work, we contribute to the knowledge of Iberian mutillids by addressing and solving the problems associated with some taxa. A new species, Physetopoda fresnoi Romano & Parejo-Pulido, sp. nov., is described from the male sex. The type material of Ph. defixa (Invrea, 1953), comb. nov., Mutilla rufipes var. dusmeti Mercet, 1905 (S. dusmeti stat. resurr.) confirming its synonymy with S. verhoeffi Suárez, 1959, and S. andradei Suárez, 1954, stat. resurr. =S. andradei notomelanicus Suárez, 1954, syn. nov. are revised. New synonymies are proposed for Dasylabris egregia (Klug, 1835) =Mutilla (Dasylabris) egregia var. atriventris (André, 1902), syn. nov. and Ph. nuptura (Mercet, 1905) =M. nuptura var. bofilli Mercet, 1905, syn. nov. We also provide the first Iberian records of S. inermus (Schwartz, 1984) and S. sicanus (De Stefani, 1887). The validity of the Iberian records of M. marginata Baer, 1848, Ronisia barbara (Linnaeus, 1758) and R. brutia (Petagna, 1787) is discussed and the distribution of S. pardoi Suárez, 1953 is clarified. A key to the males of the Iberian Physetopoda Schuster, 1949 and Smicromyrme Thomson, 1870 is provided. Our study underscores the need for further research on Iberian mutillids and emphasises the importance of type-material studies to clarify the mutillid species inhabiting the Iberian Peninsula and their current taxonomic status.